UPAYA MENINGKATKAN KEMAMPUAN SISWA BERBICARA TEKS PROSEDUR MELALUI MODEL PEMBELAJARAN STAD DI KELAS IX-1 SMP NEGERI 1 PADANGSIDIMPUAN TAHUN PELAJARAN 2018/2019 - Ashari Hasibuan (JURNAL LINER (Language Intelligence and Educational Research), 2022)
This study was started from the problem in speaking ability on English material of SMP Negeri 1 Padangsidimpuan where most of students have the low ability in speaking English. To improve speaking ability on English material of SMP Negeri 1 Padangsidimpuan was applied STAD model. Result of this research from each cycle could be seen from the students’ achievement in learning process, in which the average of the value on cycle I students got scores 78.61% with completeness 80.95%, meanwhile the average of the value on cycle II students got scores 86.71% with completeness 100%. It could be concluded that the using of STAD model could increase students’ speaking ability on English material at the IX-1 class of SMP Negeri 1 Padangsidimpuan. Keywords: Speaking Ability, Procedure Text, STAD model